Valve movements indicate rhythm and survival potential of scallop - Xun, Xiaogang; Wang, Jingru; Liu, Fengqing; Chen, Long; Zou, Yan; Liu, Yan; Kong, Xiangfeng; Hu, Xiaoli (Frontiers in Marine Science, 2023)
Yesso scallop, Patinopecten yessoensis, is one of the most economically important marine bivalves that has been extensively cultured on the northern coast of China. Unfortunately, recurrent mass scallop mortalities have caused enormous economic losses to farmers and industries. Therefore, the exploration of indicators to assess the survival potential of scallops is conducive to breeding new varieties for a high survival rate. However, traditional indicators related to scallop health are generally measured using laborious and time-consuming methods that often involve killing the scallops. In this study, we developed a non-invasive and real-time method for monitoring Yesso scallop valve movements. Our research demonstrated a close correlation between the behavior of valve movements and the survival potential of scallops. The frequency of valve movements was found to have a circadian rhythm with elevated frequency during 7:00–9:00 and 17:00–19:00, showing a coincident rhythm with cardiac activity. Moreover, the patterns of valve behavior indicated that intense valve movements appeared to be more equally distributed in the lifespan of long-surviving individuals. Velocity estimation of valve movement was further applied to assess its correlation with scallop vitality and mortality. The top valve movement velocity was the most important determinant of the scallop vitality coefficient, which was positively correlated with scallop survival time (R2 = 0.873, P < 0.01). The prominent variables in predicting scallop survival potential, including the scallop top velocity and thickness, were presumed to be linked to the movement associated attributes of the shell ligament and muscle, which are important determinants of valve behavior intensity. Our findings demonstrate that an understanding of the valve movements of bivalves can be of great benefit, not only in exploring scallop vitality but also in developing scallop breeding strategies.